Living with mesothelioma: A systematic review of patient and caregiver psychosocial support needs. Issue 7 (July 2022) - Breen, Lauren J.; Huseini, Taha; Same, Anne; Peddle-McIntyre, Carolyn J.; Lee, Y.C. Gary
Abstract: Objective: Practice guidelines emphasize the importance of investigating psychosocial distress in mesothelioma patients and family caregivers. We aimed to synthesize research on the psychosocial support needs of mesothelioma patients and their family caregivers. Methods: We conducted a systematic review with a narrative synthesis and quality assessment. The review process adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: MEDLINE, EMBASE, Scopus, PsychArticles, and PsycINFO were searched until December 2020 and 37 studies in English met inclusion criteria. Most (n = 24) included mesothelioma patients as a very small proportion of their cancer samples. A narrative synthesis was conducted on the 13 studies including only mesothelioma patients (n = 297) and/or caregivers (n = 82). Patients and caregivers want improvements in the diagnosis delivery and access to palliative care. Patients want emotional support, patient-centered treatment, improved information about illness progression and death, and to meet others with mesothelioma. Caregivers want one-on-one practical and emotional support. Study quality varied. Conclusions: Few studies focus on the psychosocial support needs relevant to mesothelioma. Mesothelioma patients and family caregivers highlight targeted psychosocial care as an unmet need. Practice Implications: Efforts are required to design and test psychosocial interventions for this vulnerable and overlooked group. Protocol Registration: PROSPERO (registration number CRD42020167852). Highlights: Few studies focus on the psychosocial experiences and needs relevant to mesothelioma. Mesothelioma patients and family caregivers have many unmet support needs. Patients and caregivers highlight a need for targeted psychosocial care. Research is needed to test psychosocial interventions for this vulnerable group.